Murine Notch1 is required for lymphatic vascular morphogenesis during development. Issue 7 (17th April 2014) - Fatima, Anees; Culver, Austin; Culver, Ford; Liu, Ting; Dietz, William H.; Thomson, Benjamin R.; Hadjantonakis, Anna‐Katerina; Quaggin, Susan E.; Kume, Tsutomu
<x xml:space="preserve">Abstract</x> BACKGROUND: The transmembrane receptor Notch1 is a critical regulator of arterial differentiation and blood vessel sprouting. Recent evidence shows that functional blockade of Notch1 and its ligand, Dll4, leads to postnatal lymphatic defects in mice. However, the precise role of the Notch signaling pathway in lymphatic vessel development has yet to be defined. Here we show the developmental role of Notch1 in lymphatic vascular morphogenesis by analyzing lymphatic endothelial cell (LEC)‐specific conditional Notch1 knockout mice crossed with an inducible Prox1CreERT2 driver. RESULTS: LEC‐specific Notch1 mutant embryos exhibited enlarged lymphatic vessels. The phenotype of lymphatic overgrowth accords with increased LEC sprouting from the lymph sacs and increased filopodia formation. Furthermore, cell death was significantly reduced in Notch1‐mutant LECs, whereas proliferation was increased. RNA‐seq analysis revealed that expression of cytokine/chemokine signaling molecules was upregulated in Notch1‐mutant LECs isolated from E15.5 dorsal skin, whereas VEGFR3, VEGFR2, VEGFC, and Gja4 (Connexin 37) were downregulated. CONCLUSIONS: The lymphatic phenotype of LEC‐specific conditional Notch1 mouse mutants indicates that Notch activity in LECs controls lymphatic sprouting and growth during development. These results provide evidence that similar to postnatal and pathological lymphatic vessel formation, the Notch signaling pathway plays a role in inhibiting developmental lymphangiogenesis. Developmental Dynamics 243:957–964, 2014. © 2014 Wiley Periodicals, Inc.